ANALISIS KOGNITIVISME DAN KONSTRUKTIVISME TERHADAP KRISIS LITERASI DAN KESENJANGAN DIGITAL - Intan Tri Ratna Sari; M.Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
Education in Indonesia faces the dual challenge of low cognitive literacy levels and significant disparities in digital access. According to PISA 2022 data, Indonesian students' literacy scores remain below the OECD average, indicating barriers to cognitive information processing. This article aims to analyze this problem through the perspectives of cognitive and constructivist learning theories. The method used is a case study based on secondary data with a qualitative descriptive approach, drawing on sources from national media, government reports, and scientific journals. The analysis indicates that low literacy is caused by cognitive workloads that are inappropriate for students' developmental stages, while the digital divide hinders the scaffolding process in learning. This article recommends simplifying the curriculum based on cognitive abilities and equalizing access to technology as an effort to create meaningful and inclusive learning.